Hardness-load modelling applied to multilayer galvanised coatings. (March 2016) - Benarioua, Y.; Mejias, A.; Roudet, F.; Iost, A.; Chicot, D.
Abstract : During the last past decades, galvanised steels have been extensively developed to improve corrosion resistance of steels due to their excellent chemical properties particularly in severe atmospheric conditions. The objective of this work is to predict the hardness-load variation in relation to the bath immersion time using both a multilayer coating hardness model and a layers growth modelling. The kinetic growth of each layer relates the thickness to the immersion time by a simple power law. The hardness of the intermetallic compounds is determined by applying a multilayer hardness model on classical Vickers microindentation data obtained at different indentation loads. Afterwards by combining the kinetic growth laws and the compounds hardness, it is possible to predict the surface hardness-load variation as a function of the immersion bath time.